2013
DOI: 10.1364/josaa.30.002021
|View full text |Cite
|
Sign up to set email alerts
|

Evaporating droplet hologram simulation for digital in-line holography setup with divergent beam

Abstract: Generalized Lorenz-Mie theory (GLMT) for a multilayered sphere is used to simulate holograms produced by evaporating spherical droplets with refractive index gradient in the surrounding air/vapor mixture. Simulated holograms provide a physical interpretation of experimental holograms produced by evaporating Diethyl Ether droplets with diameter in the order of 50 μm and recorded in a digital in-line holography configuration with a divergent beam. Refractive index gradients in the surrounding medium lead to a mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 18 publications
0
12
0
2
Order By: Relevance
“…This self-calibration is simple to apply since it only requires the lensless color microscopy setup. Any spherical object whose diffraction pattern can be described by a direct model (Thompson model [44] for opaque object or (Generalized) Lorenz-Mie model [52,53] for droplets, bubble or beads) can be used. For estimation of laser diode wavelengths, the suggested method makes it possible to accurately estimate two wavelengths based on the value of the third taken as a reference.…”
Section: Resultsmentioning
confidence: 99%
“…This self-calibration is simple to apply since it only requires the lensless color microscopy setup. Any spherical object whose diffraction pattern can be described by a direct model (Thompson model [44] for opaque object or (Generalized) Lorenz-Mie model [52,53] for droplets, bubble or beads) can be used. For estimation of laser diode wavelengths, the suggested method makes it possible to accurately estimate two wavelengths based on the value of the third taken as a reference.…”
Section: Resultsmentioning
confidence: 99%
“…A wake, attached to the central hologram is also clearly visible. It is caused by the deflection of the light by the refractive index gradient in the thermal -vapor concentration boundary layers and wakes developing around the droplet as discussed in Seifi et al (2013); Méès et al (2013). It was shown that the wake image visualizes well the Lagrangian relative motion of the air around the droplet (Chareyron et al, 2012;Marié et al, 2014).…”
Section: D Reconstructionmentioning
confidence: 99%
“…This is also the technique which was adopted to obtain the data presented in the next subsection. As shown in Méès et al (2013), Seifi et al (2013), the refractive index gradient affects the three central fringes of the holograms. The size of the mask is hence chosen to exclude these fringes.…”
Section: Holograms Of Evaporating Dropletsmentioning
confidence: 99%